Giant Cell Tumor of Bone: Documented Progression over 4 Years from Its Origin at the Metaphysis to the Articular Surface. (17th August 2016) - Burke, Colin; Link, Thomas; O'Donnell, Richard J.; Cho, Soo-Jin; Motamedi, Daria
Abstract : The exact location of origin for giant cell tumors of bone (GCTB) remains controversial, as lesions are not routinely imaged early but rather late when the tumor is large and clinically symptomatic. At the time of diagnosis, GCTB are classically described as lucent, eccentric lesions with nonsclerotic margins, located within the epiphysis to a greater extent than the metaphysis. Here we present a case of a biopsy proven GCTB initially incidentally seen on MRI as a small strictly metaphyseal lesion, which over the course of several years expanded across a closed physis to involve the epiphysis and abut the articular surface/subchondral bone plate.